Pengembangan Media Animasi PTG Berbantuan Adobe Animate CC Materi Satuan Panjang Kelas IV SDN 2 Cintaraja - Nabilah, Fatwa Fidia; Hendrawan, Budi; Nugraha, Mohammad Fahmi (Jurnal PGSD, 2020)
The research objective is to develop and test the effectiveness of the Adobe Animate CC hanging ladder tree animation instructional media towards the length relationship of the fourth grade students of SDN 2 Cintaraja. Type of research (R&D) and Sugiyono's adaptation development research model. There are 3 stages followed by data analysis and product revision. The data collection instruments were curriculum analysis, material analysis and similar media analysis. Data collection techniques using qualitative and quantitative data. The development data analysis technique used questionnaires and questions, namely the pretest and posttest. The results of the test scores were calculated using the Paired Sample T-Test analysis technique, the results obtained were t> t or 19.733> 2.079 meaning that Ho was rejected and Ha was accepted, meaning that there was a significant difference between before and after using the media. The posttest average score was 84.04 above the value (KKM), namely 75.00. The posttest score of 84.04 is greater than the pretest value of 51.66 so that the learning media is said to be feasible and effective to use.